Fused deposition modeling 3D printing as a method for manufacturing personalized medicines - Jolanta Pyteraf; Witold Jamróz; Mateusz Kurek; Renata Jachowicz (Polish Pharmaceutical Society, 2023)
Additive manufacturing techniques, especially methods based on the deposition of thermoplastic material such as Fused deposition modeling (FDM), are gaining more and more applications. Due to the large variety of materials used and the quick ability to produce small batches of products in accordance with the computer project, these methods are considered as a method of dosage forms manufacturing both on an industrial scale as well as in small batches. Numerous scientific studies related to the printing of dosage forms of various structures have been published in recent years. These studies concern both preparations for oral administration, such as tablets and capsules with modified and immediate release of the active pharmaceutical ingredient (API), as well as intraocular dosage forms and wound dressings. In the case of the FDM method, the printing process is preceded by the material preparation step. It consists of the preparation of a drug-loaded filament in the hot-melt extrusion process. After feeding the filament into the printer's head, it is re-heated, liquefied, and precisely deposited on the printer's table in order to reproduce a spatial structure according to the computer design. The filaments used in the printing process of the dosage form should be characterized by, among others: appropriate mechanical strength, high diameter uniformity, and long-term stability. Apart from thermoplastic polymers, other excipients are also used in the composition of the formulation, i.e., disintegrants, plasticizers, and compounds inhibiting the API phase transformations in the polymer matrix. Printed dosage forms are often characterized by a complex internal spatial structure. For this reason, the API release depends not only on the properties of the excipients used, but especially on printouts' surface area and porosity, as well as the shape and infill density. In addition, conditions during the extrusion and 3D printing processes may result in the dissolution of API in the polymer carrier and accelerate its dissolution rate.